The Gondwanan Origin of Tribosphenida (Mammalia). Issue 3 (2nd October 2022) - Flannery, Timothy F.; Rich, Thomas H.; Vickers-Rich, Patricia; Veatch, E. Grace; Helgen, Kristofer M.
Abstract: A review of the Southern Hemisphere Mesozoic tribosphenic mammal fossil record supports the hypothesis that Tribosphenida arose in the Southern Hemisphere during the Early Jurassic, around 50 million years prior to the clade's reliably dated first appearance in the Northern Hemisphere. Mesozoic Southern Hemisphere tribosphenic mammals are known from Australia, Madagascar, South America and the Indian subcontinent, and are classified into three families: Bishopidae (fam. nov.), Ausktribosphenidae and Henosferidae. These are stem therians, and considerable morphological evolution occurred within the lineage between the Jurassic and late Early Cretaceous. Important dental modifications include a graduated transition between premolars and molars, development of molar wear facets V and VI, loss of facets for postdentary bones, reduction in the Meckelian groove and development of a true dentary angle. Previous classifications of Southern Hemisphere tribosphenic mammals are ambiguous because information from the upper dentition has been lacking. Upper molars attributed to the late Early Cretaceous (Albian) Southern Hemisphere group Bishopidae fam. nov. are now known to possess a prominent protocone and stylar cusp C. We thus consider bishopids to be the sister group to Theria. Timothy F. Flannery [tim.flannery@textpublishing.com.au ], Kristofer M. Helgen [Kris.Helgen@Australian.Museum ], Australian Museum, 1 William St Sydney 2000, Australia; Thomas H. Rich [trich@museum.vic.gov.au ], Museums Victoria, PO Box 666, Q28 Melbourne, Victoria 3001, Australia; Patricia Vickers-Rich [pat.rich@monash.edu ; prich@swin.edu.au ], School of Earth, Atmosphere and Environment, Monash University, Victoria 3800, Australia; Swinburne University of Science and Technology, Department of Chemistry and Biotechnology, Hawthorn, Victoria 3122, Australia; Elizabeth Grace Veatch [elizabeth.veatch@gmail.com ], National Museum of Natural History, Smithsonian Institution, Washington, DC 20013, USA.